Teach yourself visually powerpoint 2010 - Wood, William (Teach yourself visually, 2010)
Provides step-by-step screen shots that show you how to tackle more than 130 PowerPoint 2010 tasks. Each task-based spread covers a single technique, sure to help you get up and running on PowerPoint 2010 in no time